2002
DOI: 10.14742/ajet.1879
|View full text |Cite
|
Sign up to set email alerts
|

Interaction online: Above and beyond requirements of assessment

Abstract: Today's literature is filled with new paradigms for learning, specifically in relation to the increasing adoption of computer mediated techniques for interactive learning. In many cases, learning may now be enhanced through the experience of a shared online environment for critical discussion, knowledge building and the establishment of supportive social communities. Research data obtained from social science students at Southern Cross University over two semesters reveals students' perceptions of the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 10 publications
0
10
0
1
Order By: Relevance
“…For example, O'Reilly and Newton (2002) found the majority of their 90 survey respondents highly valued interaction with peers and reported a wide range of benefits including mutual support, friendships, a reduced sense of isolation and new insights into the concepts being studied. Yildiz and Chang (2003) similarly reported that most of the 20 respondents to their survey perceived they learnt a lot from their peers and received more immediate and higher quality peer feedback than in face to face courses.…”
Section: Online and Distance Education Students' Attitudes Towards Inmentioning
confidence: 99%
“…For example, O'Reilly and Newton (2002) found the majority of their 90 survey respondents highly valued interaction with peers and reported a wide range of benefits including mutual support, friendships, a reduced sense of isolation and new insights into the concepts being studied. Yildiz and Chang (2003) similarly reported that most of the 20 respondents to their survey perceived they learnt a lot from their peers and received more immediate and higher quality peer feedback than in face to face courses.…”
Section: Online and Distance Education Students' Attitudes Towards Inmentioning
confidence: 99%
“…synchronous communication Synchronous conferences, familiar to the recreational Internet user as "chat rooms," "chat lines," and instant messaging systems [28], also have been used in various ways in online courses ( [16]; [35]; [37]). Synchronous conferences have the advantages of open access to the floor, interactivity, immediacy, and retention of a written record ( [12]; [40]).…”
Section: Overall Meaningful Interaction and The Use Ofmentioning
confidence: 99%
“…Group size is critical to the creation of a community of online learners as is the ability of students to break down barriers to enter into online debate, Stacey (1999). Aspden and Helm (2004), O'Reilly, M., & Newton, B. (2002) all point out the correlation between student participation in online discussion fora and the relevance of their discussions to what is spoken about in the classroom.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An issue with learning through simulation is the difficulty of assessing students. O'Reilly and Newton (2002) attest to the "assessment factor", that is that students find it very difficult to motivate themselves to engage in work which they know does not lead directly to assessment.…”
Section: Literature Reviewmentioning
confidence: 99%